A behavioral and neurobiological assessment of episodic-like memory in aged and young Sprague-Dawley rats - Stuebing-Keith, Sarah (Kansas State University, 2021)
Episodic memory loss is a cognitive deficit commonly seen in both natural aging and pathological processes like dementia of the Alzheimer’s type. Episodic-like memory, the animal counterpart of episodic memory, provides a unique avenue to study both the behavioral and neurobiological components of this cognitive decline using aged rodents. This memory type consists of “what”, “when”, and “where” components that must be correctly integrated for proper memory utilization. Novel behavioral interventions were based off of these components to determine if supporting or enhancing just one of these episodic-like memory components could improve the episodic-like memory mechanism as a whole. More specifically, this study aimed to determine if these behavioral interventions could improve episodic-like memory in both aged and young rats. The interventions did show promising episodic-like memory improvement in the young rat cohort and suggested that further training with the interventions may have improved memory performance in both aged and young animals. The second goal of the study was to utilize immunohistochemical analysis of choline acetyltransferase (ChAT) in the hippocampi of aged and young rats to identify neurobiological targets of episodic-like memory decline, as well as to determine how they relate to behavioral task performance deficits. No significant neurobiological relationships of ChAT to task performance were found within the potentially affected aged group. These findings suggest that behavioral interventions could be utilized to delay the loss of episodic memory occurring in both aging and dementia, especially if applied early, and that multimodal neurobiological targets may be more effective than unitary acetylcholine-targeted pharmacological therapy.
Keywords: Episodic-like memory; Aging; Behavioral interventions; Sprague-Dawley rats; Neurobiology